Using human-centered design to improve the quality of vaccine communication. (30th September 2020) - Rath, B
Abstract: In recent years, one-on-one vaccine communication has become more important that ever. Research has shown that an intact parent-paediatrician relationship is the most important predictor for positive attitudes toward immunisation. Yet, much of the discussion around the benefits of vaccines and the risk of vaccine preventable diseases has also moved online. New communication channels and discussion fora are evolving rapidly, and their use may differ significantly among different sociodemographic groups. These recent developments have implications for the work of policy makers. Public health messaging will need to be tailored to different subsectors of the population, such as those primarily interested in maternal-infant care, adolescent health, or travel medicine. Mobile applications, telemedicine, video blogs, and other digital fora provide room for science-informed vaccine communication extending beyond the brief conversations at the doctor's office. Each mode of communication may have its own impact, but pediatricians will need to get involved in bridging the communication gap between policy makers and public health agencies on one hand, and children and families on the other. We will discuss the results of recent projects undertaken by the Vienna Vaccine Safety Initiative using the innovation technique of Design Thinking to move the experience of children and their caretakers back into the center of the conversation. We will provide practical examples of human-centered design i) to improve the understanding of individual-level disease severity in flu patients, ii) to empower parents to keep the vaccination records in their family up-to-date, iii) to improve safety reporting at the point of care, and iv) to enable migrant populations to report missed immunizations and other health needs. We will invite active discussion with the audience while providing critical analysis of lessons learnt and implications for health policy and future research.